Pemberdayaan Guru SD melalui Pelatihan Menulis Karya Ilmiah - Rihlah, Jauharotur; Rulyansah, Afib; Budiarti, Rizqi Putri Nourma (UKInstitute, 2022)
Teachers are required to write scientific papers as part of their work. Because not all teachers are proficient writers of scientific papers, this is a problem in the field of education. Most of the teachers at SDN Tambelang 1 and SDN Curahsawo 3 Probolinggo Regency still have difficulty writing scientific papers, according to a preliminary survey. As a result of these problems, teachers should be provided with training and assistance in article creation. The curriculum of the training and mentoring program is based on volunteer work in the community. The teaching team of FKIP PGSD Universitas Nahdatul Ulama Surabaya is involved in the service project. Face-to-face and online coaching and teaching activities are combined in this way. Both theoretical and practical instructions are given in the first stage; assistance on how to submit papers for publication in the following scientific publications. Teachers' understanding and scientific writing skills can benefit from this volunteer work in the community and become more refined as a result. Teachers, on the other hand, have the option of submitting papers to scientific publications as part of their duties as educators. Abstrak: Guru wajib menulis karya ilmiah sebagai bagian dari pekerjaannya. Karena tidak semua pengajar adalah penulis karya ilmiah yang mahir, hal ini menjadi persoalan di bidang pendidikan. Sebagian besar pengajar di SDN Tambelang 1 dan SDN Curahsawo 3 Kabupaten Probolinggo masih kesulitan menulis karya ilmiah, menurut survei pendahuluan. Sebagai akibat dari masalah ini, Guru harus diberikan pelatihan dan bantuan dalam pembuatan artikel. Kurikulum program pelatihan dan pendampingan didasarkan pada kerja sukarela di masyarakat. Tim Pengajar FKIP PGSD Universitas Nahdatul Ulama Surabaya terlibat dalam proyek pengabdian tersebut. Kegiatan pembinaan dan pengajaran tatap muka dan online digabungkan dengan cara ini. Baik instruksi teoretis dan praktis diberikan pada tahap pertama; bantuan tentang cara mengirimkan makalah untuk publikasi dalam publikasi ilmiah berikut. Pemahaman guru dan kemampuan menulis ilmiah dapat mengambil manfaat dari kerja sukarela ini di masyarakat dan sebagai akibatnya menjadi lebih halus. Guru, di sisi lain, memiliki pilihan sendiri untuk mengirimkan makalah ke publikasi ilmiah sebagai bagian dari tugas mereka sebagai pendidik.